Buckling Behavior of Metallic Cylindrical Shell Structures Strengthened with CFRP Composite - Z. Draidi; T. T. Bui; A. Limam; H. V. Tran; A. Bennani (Advances in Civil Engineering)
The objective of this study is to evaluate the effect of a CFRP composite layer on the buckling behavior of metallic cylindrical shells. To enhance the bearing capacity of steel shells, classical solutions consider internal or external metallic stiffeners (stringers and/or rings) welded or riveted to the shell. Here, an external skin of composite material which wraps the whole metallic skin of the shell is studied. To be valid for metallic shells structures (storage tanks like silos) as well as for metal pipes (gas or oil pipeline), the procedure for setting up and implementing the composite must be simple. The recommended solution is therefore tested through experimental tests to find their limits and the configuration of optimal behavior. A consistent enhancement of bearing capacity is observed. This experimental base serves also to consolidate a numerical model which corroborates the experimental results. The good correlation between experimental and numerical results is confirmed for the whole loading process, for unstiffened and stiffened shells. For metallic unstiffened shell, an adequacy between experiment and simulation is noticed in the mainly membrane precritical behavior, during the buckling initiation characterized by the boundary layer problem corresponding to axisymmetric wavelength appearance near boundaries and in the postcritical domain associated to localization of the buckling mode at one extremity of the shell. For stiffened configuration, the enhancement of the bearing capacity of the shell is correctly gauged; this confirms the possibility to use finite element simulation for the design.